Resonance-enhanced multiphoton ionization (REMPI) spectroscopy of bromobenzene and its perdeuterated isotopologue: assignment of the vibrations of the S0, S1 and D0+ states of bromobenzene and the S0 and D0+ states of iodobenzene - Andrejeva, Anna; Tuttle, William D.; Harris, Joe P.; Wright, Timothy G. (American Institute of Physics, 2015)
We report vibrationally-resolved spectra of the S1  S0 transition of bromobenzene using resonance-enhanced multiphoton ionization (REMPI) spectroscopy. We study bromobenzene-h5 as well as its perdeuterated isotopologue, bromobenzene-d5. The form of the vibrational modes between the isotopologues and also between the S0 and S1 electronic states are discussed for each species, allowing assignment of the bands to be achieved and the activity between states and isotopologues to be established. Vibrational bands are assigned utilizing quantum chemical calculations, previous experimental results and isotopic shifts. Previous work and assignments of the S1 spectra are discussed. Additionally, the vibrations in the ground state cation, D0+, are considered, since these have also been used by previous workers in assigning the excited neutral state spectra. We also examine the vibrations of iodobenzene in the S0 and D0+ states and comment on previous assignments of these. In summary, we have been able to assign corresponding vibrations across the whole monohalobenzene series of molecules, in the S0, S1 and D0+ states, gaining insight into vibrational activity and vibrational couplings.